Development of a gripper for garment handling designed for additive manufacturing. (May 2021) - Jilich, Michal; Frascio, Mattia; Avalle, Massimiliano; Zoppi, Matteo
The paper presents how a robotic gripper specific for grasping and handling of textiles and soft flexible layers can be miniaturized and improved by polymeric additive manufacturing-oriented re-design. Advantages of polymeric additive manufacturing are to allow a re-design of components with integrated functions, to be cost-effective equipment for small batches production and the availability of suitable materials for many applications. The drawback is that for design validation extended testing is still necessary because of lacks in standardization and that the mechanical properties are building parameters dependent. The outcomes are a lower complexity of the design overall and lower number of components. These are pursued taking advantage of the anisotropy of the additive manufacturing processed polymer and assigning appropriate shapes and linkages in the mechanisms. Set of common materials (polylactide, polyethylene terephthalate, acrylonitrile butadiene styrene) and technical (acrylonitrile styrene acrylate, polycarbonate/polybutylene terephthalate blend) are tested to obtain data for the modelling.